MAKNA NAMA BAGI ORANG CINA WARGA NEGARA INDONESIA (Studi kasus 5 keluarga Cina) - The Significance of Names for the Indonesian Chinese in Yogyakarta (A Case Study on Five Indonesian Chinese Families) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT This thesis discusses about how the Chinese descendants in Yogyakarta give meaning to their names in the frame of Chinese culture as their native culture and in the frame of Indonesian culture. Furthermore, this thesis is intended to observe how the Chinese descendants think about the regulation of the name changing. The study is conducted in Yogyakarta considering that study about Chinese is still rarely done. Five Indonesian Chinese famiÂ¬lies who have different age, religion, profession and economic background were chosen as the subject of this case study. Meanwhile, this research is a qualitative research of which the data collecting was carried out through observation-participation and depth-interview. The result of the study showes that the basic thing of giving the meanÂ¬ing to the Chinese names depended on how they acknowledged the Chinese culture and applied them to their daily-life activities. As part of a culture, names contain certain symbols, which are the result of personal expression of the name creators. As Chinese names are seen through the frame of the Chinese culture, their Indonesian names were also seen through the frame of Indonesian culture. It is found out that the meaning of the Indonesian names was not the same with the Chinese names, and some names did not even have any meaning. The result of the study also showed that the age-differÂ¬ence played a role in the action of giving meanings to the names both Chinese and Indonesian. The action of giving meanings to the names is then related to the name changing, which was believed to be a way of assimilation process into IndoÂ¬nesian community. In general, the five Chinese families did not agree with the idea because as far as they were concerned it was more a pressure than a self-awareness. To make assimilation successful, self-awareness and willÂ¬ingness are needed instead of pressure for mingling with the Indonesians. Key words: Chinese â names â giving meaning to the names â assimilation